2012
DOI: 10.1159/000337228
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Neutrophil to Lymphocyte Ratio Predicts Poor Prognosis in Advanced Colorectal Cancer Patients Receiving Oxaliplatin-Based Chemotherapy

Abstract: Background: The aim of this study was to assess whether the neutrophil to lymphocyte ratio (NLR) and other laboratory markers may predict the prognosis of advanced colorectal cancer (CRC) patients receiving palliative chemotherapy. Methods: The study population included50 patients with far advanced or recurrent unresectable CRC who received oxaliplatin-based combination chemotherapy as first-line treatment in our hospital between June 2005 and November 2010. Seven clinical variables and 7 laboratory indices be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(50 citation statements)
references
References 78 publications
(47 reference statements)
2
46
1
1
Order By: Relevance
“…The NLR has also been shown to predict outcomes in patients with advanced colorectal cancer who are receiving chemotherapy, and it has been used as a predictor of tumor recurrence and progression. 9,10 However, the prognostic potential of the NLR may not apply to all therapeutic scenarios. For example, in an unplanned secondary analysis of patients with muscle-invasive bladder treated in a randomized phase III study with or without neoadjuvant chemotherapy, the NLR was not found to be prognostic of overall survival benefit from neoadjuvant chemotherapy.…”
Section: Prognosis: Linking Inflammation With Oncology Outcomesmentioning
confidence: 99%
“…The NLR has also been shown to predict outcomes in patients with advanced colorectal cancer who are receiving chemotherapy, and it has been used as a predictor of tumor recurrence and progression. 9,10 However, the prognostic potential of the NLR may not apply to all therapeutic scenarios. For example, in an unplanned secondary analysis of patients with muscle-invasive bladder treated in a randomized phase III study with or without neoadjuvant chemotherapy, the NLR was not found to be prognostic of overall survival benefit from neoadjuvant chemotherapy.…”
Section: Prognosis: Linking Inflammation With Oncology Outcomesmentioning
confidence: 99%
“…From these, six with initial CEA higher than 5 μg/L and an increase of more than 10% were considered as surge. The median increase of CEA concentration of 22.6% (range 10.6-56.8%) was observed after a median seven (range [6][7][8][9][10][11][12][13][14] days.…”
Section: Resultsmentioning
confidence: 98%
“…However, it has been demonstrated during the past few years that relative lymphocyte numbers in the peripheral blood expressed as a ratio to other blood elements are also a powerful biomarker predictive of patient prognosis, again across a range of tumor types. Neutrophil-to-lymphocyte ratio (NLR), lymphocyte-to-monocyte ratio (LMR), platelet-to-lymphocyte ratio (PLR) and systemic inflammatory index (SII) have been shown to predict outcome in different solid tumors, including colorectal carcinoma [7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…These include the Glasgow Prognostic Score (GPS), which is based on serum CRP and albumin levels (22)(23)(24)(25)(26)(27)(28), neutrophil-to-lymphocyte ratio (NLR) (29,30), platelet-to-lymphocyte ratio (31,32), prognostic nutritional index (33,34), and prognostic index (34,35).…”
Section: Introductionmentioning
confidence: 99%